Gene network analysis reveals a core set of genes involved in the immune response of Japanese flounder (Paralichthys olivaceus) against Vibrio anguillarum infection. Issue 98 (March 2020) - Ning, Xianhui; Sun, Li
Abstract: Japanese flounder ( Paralichthys olivaceus ) is one of the most economically important marine fish cultured in north Asia. Vibrio anguillarum is a severe bacterial pathogen to Japanese flounder and many other aquaculture species. In order to understand the immune response of flounder during bacterial infection, we systematically examined the transcriptome profiles of flounder spleen at three time points after V. anguillarum challenge. More than one billion high quality reads were obtained, approximately 80.70% of which were successfully mapped to the reference genome of flounder. A total of 6060, 4688 and 4235 differentially expressed genes (DEGs) were captured at 6, 12 and 24-h post-infection, respectively. The DEGs exhibited dynamic changes in expression and were assigned into four different profiles based on expression trend. GO and KEGG analysis showed that the DEGs were enriched in various immune-related terms, including response to stimulation, immune system and pathways of cytokine-cytokine receptor interaction, Jak-STAT signaling and Toll-like receptor signaling. Furthermore, a network of highly interactive DEGs involved in 11 immune-related pathways was detected by utilizing the weighted co-expressing network analysis (WGCNA). Accordingly, 26 hub genes were discovered that constituted an elaborate immune regulatory network and functioned mainly in pathogen recognition, antigen processing, and molecular signaling. The results of this study provided the first systematical transcriptome profile of flounder in association with V. anguillarum infection and can serve as a valuable resource of target genes for future studies on the molecular mechanisms underlying the immune defense of flounder against bacterial infection. Highlights: Vibrio anguillarum -induced transcriptome profiles of flounder were investigated. A total of 8923 differentially expressed genes (DEGs) were found at 6, 12 and 24 hpi. Co-expression networks of immune relevant DEGs were constructed. Twenty-six hub genes with multiple interactions were identified. The hub genes represented mainly genes involved in immune defense against pathogens.